Material characterization and modeling of silicone putty using fractional derivatives. - Hernandez, Jaime Y. Jr (Philippine Engineering Journal)
Material characterization and modeling of materials being used in energy dissipating devices is a prerequisite in the development of accurate models which can predict the behavior of these devices. One such material in silicone putty used in the Shock Transmission Unit (STU). This paper discusses the material characterization of silicone putty using a flat plate rheometer and its modeling using a fractional derivative maxwell model under low frequencies of loading. The resulting constitutive equation is approximated using the L1-Algorithm for fractional derivatives.